A STUDY OF QUALITY OF LIFE OF PHYSICAL EDUCATION TEACHERS IN PHAYAO PROVINCE - Tampradit, Kritsada; Chailert, Pichet (Academic Journal of Thailand National Sports University, 2022)
The purposes of this study were to study the level and personal factors related to the quality of life and compare the quality of life of physical education teachers classified by sex, income and age range. The instrument used in this research were questionnaires of World Health Organization Quality of Life Brief- Thai with reliability 0.95. The sample group was 201 physical education teachers in the office of the basic education commission, Phayao province, academic 2020. The data were analyzed by using mean and standard deviation, Pearson product moment correlation, Independent Sample t - test and One - way ANOVA were employed for significance at the .05 The research findings were as follow: The quality of life of physical education teachers in Phayao Province in terms of quality of life and overall health was at the moderate level (92.86) and the quality of life in terms of physical, psychological, social relationship and environmental domain also was at the moderate level with 24.06, 21.70, 11.40 and 28.40 respectively. The factors correlated with quality of life of physical education teachers in Phayao province were not significantly differences. The comparison of the quality of life of physical education teachers in Phayao Province was found at the moderate level both male (M = 3.59, S.D. = 0.58) and female (M = 3.52, S.D. = 0.44), and there were no significant differences. 4. The comparison of the quality of life of physical education teachers in Phayao province classified age rang and average income; there were no significant differences.